Attitudes And Husband's Support On The Behavior Of Pregnant Women During The Covid 19 Pandemic - Indah Kurniawati; Wahyu Fuji Hariani (JKM (Jurnal Kebidanan Malahayati), 2022)
Latar Belakang: Pandemi covid 19 menjadi fenomena dunia penyebaran virus corona, situasi ini mempengaruhi kesehatan seseorang terutama pada ibu hamil. Di Indonesia berdasarkan data BKKBN kenaikan jumlah ibu hamil mencapai  sekitar 400.000 ibu hamil Data Dinas Kesehatan Banyuwangi terdapat peningkatan  jumlah ibu hamil tahun 2020 sebanyak  24.311 ibu hamil dan data di Puskesmas Songgon jumlah ibu hamil 881 hamil  peningkatan jumlah kasus di masa pandemi ini pastinya mempengaruhi perilaku ibu hamil. Rasa kekawatiran terutama menjelang persalinan, perlunya dukungan dari berbagai pihak untuk mengurangi resiko kehamilan.Tujuan : Penelitian ini untuk mengetahui hubungan sikap dan dukungan suami terhadap perilaku ibu hamil di masa pandemi covid 19.Metode :Penelitian iniadalah kuantitatif  dengan pendekatan cross sectional, pengumpulan data dengan bersumber dari data primer dengan instrumen yang digunakan dalam penelitian ini menggunakan kuesioner dengan teknik total sampling sejumlah 43 responden di wilayah Puskesmas Songgon tahun 2021. Analisis  univariate dengan distribusi frekuensi menggunakan presentase. Analisis bivariate dengan hubungan variable pengetahuan dan dukungan suami dengan perilaku ibu hamil di masa pandemi Covid 19. Uji statistik dalam penelitian ini dengan uji chi Square. Hasil: Hasil uji statistic dengan nilai p value 0,025 <ɑ =0.05 terdapat hubungan antara sikap terhadap perilaku ibu hamil di masa pandemi covid 19 dan nilai p value 0,016 <ɑ =0.05 terdapat hubungan dukungan suami dengan perilaku ibu hamil di masa pandemi covid 19.Kesimpulan:sikap dan dukungan suami berpengaruh terdapat perilaku ibu hamil di masa pandemic Covid 19.Saran: Pemberian dukungan penuh kepada ibu hamil dalam menjalankan kehamilannya dari suami,anggota keluarga dan bidan atau tenaga kesehatan serta memberikan pelayanan kesehatan  yang baik melalui ANC (antenatal care)dalam mencegah resiko pada ibu hamil. Kata kunci: dukungan suami, kehamilan, perilaku,sikap  AbstractBackground: The COVID-19 pandemic became a worldwide phenomenon. This situation affected someone’s health, especially in pregnant women. In Indonesia, based on the National Family Planning Coordinating Agency data, the increase in the number of pregnant women reached around 400,000 pregnant women. Data from the Banyuwangi Health Service, there is an increase in the number of pregnant women in 2020 as many as 24,311 pregnant women and data at the Songgon Health Center the number of pregnant women is 881 pregnant, the increase in the number of cases during this pandemic certainly affects the behavior of pregnant women. The worry raised before delivery, the need for support from some parties to reduce the risk of pregnancy.Purpose: This study aimed to determine the correlation between husband's attitudes and support on the behavior of pregnant women during the COVID-19 pandemic.Method: This research was quantitative with a cross sectional approach, data collection was sourced from primary data with instrument in the form of questionnaires with total sampling technique as many as 43 respondents in the area of Songgon Public Health Center 2021. Univariate analysis was by frequency distribution using percentages. Bivariate analysis was the correlation of husband's knowledge and support variables with the behavior of pregnant women during Covid 19 pandemic. The statistical test used chi square test.Result: The results of statistical test with p value of 0.025 <ɑ = 0.05 there was a correlation between husband’s attitudes towards the behavior of pregnant women during the COVID 19 pandemic and p value of 0.016 <ɑ = 0.05 there was a correlation between husband's support and the behavior of pregnant women during COVID 19 pandemic.Conclusion: Husband’s attitudes and support had an effect on the behavior of pregnant women during the COVID 19 pandemic.Suggestion: Providing full support to pregnant women in carrying out their pregnancies from husbands, family members and midwives or health workers as well as providing good health services through ANC (antenatal care) is needed to prevent the risks to pregnant women. Keywords: attitudes, behavior, husband’s support, pregnancy.